PERANCANGAN SISTEM INFORMASI PENDATAAN DANPENYALURAN PROGRAM BERAS SEJAHTERA (STUDI KASUS: Kp.LEUWIBILIK, DESA TAJUR, KECAMATAN CITEUREUP, BOGOR) - Putra Agung Wibisono, - (2018)
This research is conducted to Design Information System Data Collection and Distribution Rice Prosperous Program (RASTRA) for proper distribution of target and post-distribution reporting clear. This system is Web Based and case study in Tajur Village, Citeureup Sub District, Bogor. This system is made because the distribution is still less targeted and less effective and efficient, and post- distribution reporting is less transparent. thus making the researcher want to design an information system to assist the village agency in managing Rastra. The method used in the development of this information system is Prototype. In performing problem analysis using PIECES parameters (Performance, Information, Economic, Control, Effeciency, and Service) and design the design model using UML (Unified Modeling Language) modeling. In addition in making this web-based applications, researchers using PHP and MySQL programming language. With the existence of web-based application system is expected to be a solution for the village agencies in conveying and presenting information about the Raskin program environment Tajur Village, District Citeureup, Bogor